2018
DOI: 10.1038/s41598-018-30447-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Novel Regulation of N-myristoyltransferase by Mammalian Target of Rapamycin in Breast Cancer Cells

Abstract: Breast cancer is the most common cancer in women worldwide. Hormone receptor breast cancers are the most common ones and, about 2 out of every 3 cases of breast cancer are estrogen receptor (ER) positive. Selective ER modulators, such as tamoxifen, are the first line of endocrine treatment of breast cancer. Despite the expression of hormone receptors some patients develop tamoxifen resistance and 50% present de novo tamoxifen resistance. Recently, we have demonstrated that activated mammalian target of rapamyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…It also indicates that mTORC1 is a novel effector of NMT1 in cancer cells. This is in agreement with the finding that mTOR inhibition increases NMT1 expression in breast cancer cells 47 , possibly due to a compensatory mechanism to increase LAMTOR1 myristoylation and restore mTORC1 activity in cells treated with mTOR inhibitors. We observed that NMTi treatment not only prevented LAMTOR1 localization, but also decreased total LAMTOR1 protein levels.…”
Section: Discussionsupporting
confidence: 92%
“…It also indicates that mTORC1 is a novel effector of NMT1 in cancer cells. This is in agreement with the finding that mTOR inhibition increases NMT1 expression in breast cancer cells 47 , possibly due to a compensatory mechanism to increase LAMTOR1 myristoylation and restore mTORC1 activity in cells treated with mTOR inhibitors. We observed that NMTi treatment not only prevented LAMTOR1 localization, but also decreased total LAMTOR1 protein levels.…”
Section: Discussionsupporting
confidence: 92%
“…Such models can be analysed using the tools presented here. Results obtained will form a basis for model comparison, which provides a powerful tool to identify mechanisms that drive dynamics (see for example [19,26,34,33]). With a given set of experimental data, such models can be fitted, for example via a Bayesian approach [4].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The overexpression of p16 INK4A ultimately engages RB to suppress growth and cell cycle progression and promotes oncogene-induced senescence [14]. The dysregulation of INK4 has been associated with poor response to endocrine therapy [15]. Moreover, it has been observed that the loss of the tumor suppressor gene Cyclin Dependent Kinase Inhibitor 2A ( CDKN2A ), which encodes for p16 INK4A, is one of the most common abnormalities in BC, causing uncontrolled activation of CDK4/6, which leads to abnormal cell proliferation [15,16].…”
Section: Biological Mechanisms Behind Endocrine Resistancementioning
confidence: 99%
“…The dysregulation of INK4 has been associated with poor response to endocrine therapy [15]. Moreover, it has been observed that the loss of the tumor suppressor gene Cyclin Dependent Kinase Inhibitor 2A ( CDKN2A ), which encodes for p16 INK4A, is one of the most common abnormalities in BC, causing uncontrolled activation of CDK4/6, which leads to abnormal cell proliferation [15,16]. Everolimus, an mTOR inhibitor, was, in combination with AI, the first target drug developed with the aim of overcoming endocrine resistance [17].…”
Section: Biological Mechanisms Behind Endocrine Resistancementioning
confidence: 99%